In-plane mixed-dimensional 2D/2D/1D MoS2/MoTe2/Mo6Te6 heterostructures for low contact resistance optoelectronics - Kim, Hyeonkyeong; Kim, Young Chul; Ahn, Yeong Hwan; Yoo, Youngdong (Chemical Engineering Journal, 2023)
Mixed-dimensional heterostructures formed by combining 2D materials and other dimensional (0D, 1D, and 3D) materials provide new opportunities for various applications owing to their novel properties. However, in-plane mixed-dimensional heterostructures have been rarely investigated. Here, we report a novel flux-controlled chemical vapor deposition method for synthesizing in-plane mixed-dimensional heterostructures composed of monolayer MoS2 and low-dimensional Mo/Te compounds. By adjusting the Te flux and growth time, we controlled the composition, dimension, and phase of the Mo/Te compounds interfaced with the MoS2. While in-plane 2D/1D MoS2/Mo6Te6 and 2D/2D/1D MoS2/2H MoTe2/Mo6Te6 heterostructures were obtained with a low Te flux, in-plane 2D/2D MoS2/mixed 2H-1T’ MoTe2 and 2D/2D MoS2/2H MoTe2 heterostructures were synthesized with a high Te flux. We investigated the transport properties of the devices fabricated with in-plane mixed-dimensional 2D/2D/1D MoS2/2H MoTe2/Mo6Te6 heterostructures and imaged localized electronic band structures using scanning photocurrent microscopy. Under the low bias condition, the device exhibited an Ohmic-like behavior, which has not been achieved in conventional devices with stacked van der Waals junctions. Under the high bias condition, the device showed a rectifying behavior because of band-bending formed at the heterojunctions; this is consistent with the electronic band-alignment expected from the bandgap and electron affinity of the materials.
Keywords: Bias conditions; Chemical vapor deposition methods; Edge contacts; Flux-controlled; Growth time; Low dimensional; Mixed-dimensional heterostructure; Property; Synthesised; Te compounds; Edge contact; Mixed-dimensional heterostructures; Mo6Te6; MoS2; MoTe2